2021
DOI: 10.1155/2021/5556122
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Tanshinone IIA Sulfonate Ameliorates Injury‐Induced Oxidative Stress and Intervertebral Disc Degeneration in Rats by Inhibiting p38 MAPK Signaling Pathway

Abstract: Objective. Sodium tanshinone IIA sulfonate (STS) is a water-soluble derivative of tanshinone IIA, a representative traditional Chinese medicine. The aim of the study was to investigate the capability of STS to reverse injury-induced intervertebral disc degeneration (IDD) and explore the potential mechanisms. Methods. Forty adult rats were randomly allocated into groups (control, IDD, STS10, and STS20). An IDD model was established by puncturing the Co8-9 disc using a needle. Rats in the STS groups were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
(58 reference statements)
0
19
0
Order By: Relevance
“…AQP-3 could inhibit the expression of Bax and caspase-3 genes and alleviate NP cells’ apoptosis under oxidative damage. The inhibition of the p38 MAPK pathway by STS and AQP-3 has implications in further applications for alleviating the development of DDD ( 125 , 126 ).…”
Section: Therapymentioning
confidence: 99%
“…AQP-3 could inhibit the expression of Bax and caspase-3 genes and alleviate NP cells’ apoptosis under oxidative damage. The inhibition of the p38 MAPK pathway by STS and AQP-3 has implications in further applications for alleviating the development of DDD ( 125 , 126 ).…”
Section: Therapymentioning
confidence: 99%
“…Apoptosis is initiated and executed by the caspase family of cysteine proteases located in the cytosol. The overexpression of Bcl-2 and the knockdown of caspase3 both prevent apoptosis and degenerative changes [ 35 , 36 ]. Following the treatment with TAK-715, Bcl-2 expression significantly increased, but Bax and cleaved-caspase3 expression decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of p38α and p38β were remarkably higher in the IVDD tissue compared with that in the normal NP tissue, while the expression level of p38δ was lower in the IVDD tissue compared with that in the normal NP tissue and could only be detected in half of the IVDD tissue; further, the expression level of p38γ was lower than that of p38δ. In vivo, Dai et al 42 showed that the expression level of the activated p38 MAPK was significantly higher in the rat IVDD groups compared with the control group ( p < 0.01). Cheng et al 43 found a significant increase in the expression level of activated p38 in degenerated rat NP tissues.…”
Section: Expression Changes Of P38 Mapk In Ivddmentioning
confidence: 99%